2007
DOI: 10.1111/j.1466-8238.2007.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Around the world in 10 million years: biogeography of the nearly cosmopolitan true toads (Anura: Bufonidae)

Abstract: Aim The species-rich family of true toads (Anura: Bufonidae) has been the focus of several earlier studies investigating the biogeography of geographically widespread taxa. Herein, we employ newly developed Bayesian divergence estimate methods to investigate the biogeographical history of this group. Resulting age estimates are used to test several key temporal hypotheses including that the origin of the bufonid clade pre-dates Gondwanan vicariance (~105 million years ago, Ma). Area cladograms are also invoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
4
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 65 publications
11
128
4
8
Order By: Relevance
“…Both mitochondrial and nuclear analyses recovered four main clades consistent with broad biogeographic regions and previous analyses of bufonids (Pauly et al 2004;Pramuk et al 2008;Van Bocxlaer et al 2010;Pyron and Wiens 2011). These clades include the Nearctic Anaxyrus, the Middle American Incilius, the South American Rhinella, and a fourth Old World clade that includes the African Amietophrynus and the Asian Duttaphrynus (we use these names as unranked clade names within the genus Bufo).…”
Section: Mitochondrial Introgressionsupporting
confidence: 81%
See 1 more Smart Citation
“…Both mitochondrial and nuclear analyses recovered four main clades consistent with broad biogeographic regions and previous analyses of bufonids (Pauly et al 2004;Pramuk et al 2008;Van Bocxlaer et al 2010;Pyron and Wiens 2011). These clades include the Nearctic Anaxyrus, the Middle American Incilius, the South American Rhinella, and a fourth Old World clade that includes the African Amietophrynus and the Asian Duttaphrynus (we use these names as unranked clade names within the genus Bufo).…”
Section: Mitochondrial Introgressionsupporting
confidence: 81%
“…Bufo (Rhaebo) haematiticus was specified as the outgroup. All recent studies of bufonids have identified our ingroup as monophyletic with respect to B. haematiticus (Pauly et al 2004;Frost et al 2006;Pramuk et al 2008;Van Bocxlaer et al 2010;Pyron and Wiens 2011). The 35 ingroup species were selected because crossing data were available and either existing sequences or tissue samples could be obtained to construct a multilocus dataset.…”
Section: Taxon Samplingmentioning
confidence: 73%
“…Furthermore, it is worth noting that the amphibian timetree as a whole indicates, as one would expect from the dispersal abilities of these animals, that the large-scale, continental distribution of amphibians is mostly well explained by the breakup of Laurasia and Gondwana (Bossuyt et al 2006;Pramuk et al 2008;Zhang and Wake 2009;Pyron 2014). In other words, the various over-water dispersal events are inferred within a time frame that generally supports a plausible history of vicariance, in line with much geological evidence.…”
Section: São Tomé and Príncipesupporting
confidence: 61%
“…Certainly, bidirectional dispersal across the Holarctic is possible for ectotherms, as seen in toads, ranid and hylid frogs, which crossed the between the OW and NW several times (Smith et al, 2005;Wiens et al, 2006Wiens et al, , 2009Pramuk et al, 2008). One possibility for the squamates is that return colonization from the NW was simply not possible due to degrading habitat at the end of Miocene in Beringia, an expectation of the CBDH.…”
Section: Xenochrophis Vittatusmentioning
confidence: 99%